Surgical management decreases disease recurrence risk in recurrent pyogenic cholangitis. Issue 9 (11th December 2017) - Tan, Hwee Leong; Koh, Ye Xin; Lye, Weng Kit; Lee, Ser Yee; Goh, Brian Kim Poh; Tan, Siong San; Chiow, Adrian Kah Heng; Chan, Chung Yip
Abstract : Background: Recurrent pyogenic cholangitis (RPC) has a high risk of disease recurrence. We present our experience with RPC and examine the factors associated with disease recurrence. Methods: We performed a retrospective review of all patients with RPC treated at two tertiary institutions between January 1990 and December 2013. Patients with liver atrophy and/or abscess were categorized as being associated with parenchymal disease (PD). Results: We studied 157 patients with a median age of 59.0 (interquartile range (IQR): 47.0–70.0) years and a median follow‐up duration of 71.0 (IQR: 26.0–109.0) months. There were 64 (40.8%) and 93 (59.2%) patients with and without associated PD, respectively. Disease recurrence rate was 43.9% in our overall cohort through the course of follow‐up. Surgical treatment was an independent prognostic factor for decreased disease recurrence risk (hazard ratio (HR) 0.40, 95% confidence interval (CI) 0.18–0.87, P = 0.021). Stratified analysis revealed that liver resection was prognostic for lower risk of disease recurrence among patients with PD (HR 0.38, 95% CI 0.15–0.94, P = 0.036), while biliary bypass was prognostic for lower risk of disease recurrence among patients without PD (HR 0.30, 95% CI 0.15–0.61, P = 0.001). The overall post‐operative complication rate among surgically treated patients was 31.1%, and the presence of bilobar stones was found to be independently associated with higher odds of post‐operative complications (odds ratio 3.51, 95% CI 1.26–9.81, P = 0.017). Conclusion: Surgical treatment is associated with decreased recurrence risk in RPC, but with significant post‐operative morbidity. Where surgery is deemed appropriate, patients with and without PD are likely to benefit from liver resection and biliary bypass, respectively.